The construct of state practices: excavating Municipal relationships with waste pickers, the case of the City of Johannesburg. - Dladla, Nomathemba Elizabeth (My University, 2018)
This research focues on the City of Johannesburg’s Environment Infrastructure and Service Delivery Department as well as Pikitup and how they have been engaging with reclaimers in the city of Johannesburg. There was a need to conduct research on the relationship between the state and the reclaimers in Johannesburg because of the loopholes and inconsistencies in the practices and forms of management that shape Pikitup’s and COJ’s programmes to work with reclaimers (SACN, 2016). The reclaimers that began to work with the City in programmes such as the Separattion at Source were not included in the planning processes and City officials did not have guidelines that assist them in working with reclaimers. This research explores the practices of the state that are often missing from accounts (documents) of service delivery and engagement with reclaimers. Therefore, one of the main concepts unpacked in this research are state practices and instruments and how they produce certain norms (Sharma and Gupta, 2009; Olivier de Sardan, 2009; Bénit-Gbaffou, 2016). The notion of “integration” that links to other concepts such as partnership, formalisation, co-production and empowerment have also been looked into. For the purpose of this study the following question will be addressed: How have state practices of City officials shaped and influenced the “integration” of reclaimers in the city Johannesburg?. The research was explored through qualitative and the ethnographic research methods. The City of Johannesburg has been going through a major shift in relation to its political context. Therefore, the study also investigates the current priorities of the City with regards to reclaimers. I demonstrate how the challenges faced by City offiials are as a resut of lacking guidelines and strategies. These challenges have also caused the fluidity of the City official’s commitment to working with reclaimers. This has been explored principally through Pikitup and EISD officials in the City of Johannesburg.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Urban Studies, September 2018
Keywords: Recycling (Waste, etc.)--South Africa--Johannesburg; Integrated solid waste management